Abortion during the Covid-19 pandemic in Indonesia: nation’s responsibility in fulfilling women’s rights related to sexual health and reproduction - M. Kenza Radhya E.A; Noering Ratu Fatheha Fauziah Sejati; Dicky Eliakim Siringoringo (Cogent Social Sciences)
Women’s sexual and reproductive health plays an important role in fulfilling human rights. Even during Covid-19 pandemic, it is important to fulfill sexual and reproductive health rights. However, many human rights violations occur among minority groups, especially women in cases of abortion. During pandemic, based on data The National Population and Family Planning Agency (BKKBN) of Indonesia, there has been a decrease by 40% in contraceptive use and an increase in unwanted pregnancies by 15–30%. The number of unwanted pregnancies will increase and make abortion an option for every woman. Social restrictions in Covid-19 situation create challenges and vulnerabilities for women, which has had a significant impact from the pandemic in fulfilling social justice. This article aims to analysis how abortion during Covid-19 is handled based on a human rights approach and how Indonesia as a state to fulfills its responsibilities in overcoming the problem of abortion during Covid-19. The research method used qualitative study by combining doctrinal legal research and empirical legal research. It was concluded that the rise in abortion cases during the Covid-19 pandemic shows that the state has not been able to fulfill the state’s responsibility to fulfill, to respect and to protect human rights, especially women’s sexual and reproductive health rights.